The Psychology of Character. - Allers, Rudolf (Catholic University of America Press (Bibliovault) : Catholic University of America Press, 2022)
'How we became what we are. There are many explanations. One plausible account is found in the work of Rudolph Allers who writes about the European intellectual landscape from 1850 to the opening decades of the twentieth century...Allers is not alone in recognizing that a true account of human nature may await the recovery of classical antiquity. From Plato and Aristotle, modernity may learn that the immaterial or spiritual component of human nature is not empirically discerned but reasoned to from empirical evidence.'- from the foreword by Jude Dougherty--